Prevalence, sociodemographics, and indications for extraction of impacted mandibular third molar in Najran, a Southern Saudi Arabian city - Ramat Oyebunmi Braimah; Dawood Ali-Alsuliman; Hakeem Olatunde Agbaje; Yahyah Alsalah; Harit Kanwar Sharma; Nahal Mamdouh Alsawas (Wolters Kluwer Medknow Publications, 2021)
Introduction: Third molar impaction is a common condition associated with a high standard of living. Aim: The main objective of the study was to document the prevalence of mandibular third molar impactions among the Najran populace. Materials and Methods: This is a retrospective study reviewing computerized medical records and panoramic radiographs of patients presenting for the extraction of mandibular third molars. Ethical approval was granted from the General Directorate of Health Affairs, Ministry of Health, Najran region. Data such as demographics, indications for third molar removal, position, and pattern of third molar impaction were collected. Data were stored and analyzed using IBM SPSS software version 25 for IOS (Armonk, NY: IBM Corp). Results and Discussion: Amongst 6205 extractions, 1024 mandibular third molar extractions were carried out with a prevalence rate of 16.5%. There were 609 (59.5%) female and 415 (40.5%) male (F:M = 1.5:1). The age ranged from 17 to 69 years (mean ± standard deviation, 31.4 ± 9.6 years), with the majority (52.1%) in the age group of 21-30 years. One hundred and ninety-one (18.6%) of the pericoronitis cases were associated with vertical impaction, while the majority of the caries were associated with mesioangular impaction (323 [31.5%]). Mesio-angular impactions (40.8%) and Level A depth (477 [46.6%]) were the most common. Class I ramus relationship had the highest distribution (561 [54.8%]). Conclusion: We have reported a prevalence rate of 16.5% of impacted mandibular third molar in mostly 21-30 years of age with female preponderance. Pericoronitis was the main indication for surgical extraction.